(untitled) (Acta Entomologica Serbica, 2023)
Monitoring spiders with pitfall traps often only includes data collected during the vegetation period. Herein, we present the results of long-term sampling at Erdelj, Fruška Gora Mountain, over 19 months in 2011/2012. Special emphasis was placed on the winter period. At three sampling sites, a meadow, an area of shrubs and a deciduous forest, 1113 adult spiders of 116 species were identified. Thirty-four species are new records for the mountain; six of them are new to Serbia. The meadow yielded the highest number of species (59), with a high proportion (40%) of species collected only in this habitat type. Eleven species were found to be active mostly or exclusively in winter. Four of them were so-called rare spiders and two of them are new records for Serbia. Of all recorded species, five are on the list of strictly protected spiders in Serbia and could be used as an additional argument for environmental protection.